DEVELOPMENT OF NEARPOD BASED INTERACTIVE MULTIMEDIA IN FIFTH GRADE IPAS LEARNING ON THE ECONOMIC CONDITIONS IN MY REGION - Evi Fitria Cahyaningrum (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
In the elementary education curriculum, learning about economic activities is often considered difficult for elementary school students to understand. Therefore, the use of nearpod-based interactive multimedia can increase student engagement with abstract and contextual materials such as economic conditions in their area. The purpose of this study is to develop nearpod-based interactive multimedia in fifth grade elementary school science learning. The researcher used the type of research and development Research and Development (R&D) referring to the Borg and Gall model that has been modified by Sugiyono. The results of this product development obtained a percentage of 96.66% valid category from material experts, 98.18% very valid category from design experts, 91.11% very valid category from language experts, and 93.33% very valid category from education practitioners. Based on the results of the pretest posttest, the N-Gain value was obtained = 0.88. When converted into n-gain interpretation, nearpod-based interactive multimedia is included in the category of having high effectiveness. Student and teacher responses obtained a percentage of 100%, so that the nearpod-based interactive multimedia that has been developed is categorized as very practical.